2004
DOI: 10.1073/pnas.0308369101
|View full text |Cite
|
Sign up to set email alerts
|

Intact type 1 immunity and immune-associated coagulative responses in mice lacking IFNγ-inducible fibrinogen-like protein 2

Abstract: Fibrinogen-like protein 2 (Fgl2, fibroleukin) is a leukocyte product that exhibits significant homology to secreted proteins of diverse function, including growth factors, lectins, and components of extracellular matrix. Prior studies found that Fgl2 is IFN␥-inducible, possesses direct coagulant activity, and inhibits T cell proliferation and dendritic cell maturation in vitro. Here, we demonstrate that Fgl2 expression is up-regulated during type 1 immunity in vivo and establish that such up-regulation is IFN␥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 39 publications
(54 reference statements)
11
37
0
Order By: Relevance
“…Collectively, these studies support the hypothesis that (donor) endothelial cell production of mfgl2, rather than an immune-activated infiltrating leukocyte population, accounts for the fibrin deposition in allorejection (6). These data are further supported by our recent studies in xenotransplantation in which fibrin deposition associated with xenograft rejection was largely intravascular rather than associated with infiltrating inflammatory cells (21).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Collectively, these studies support the hypothesis that (donor) endothelial cell production of mfgl2, rather than an immune-activated infiltrating leukocyte population, accounts for the fibrin deposition in allorejection (6). These data are further supported by our recent studies in xenotransplantation in which fibrin deposition associated with xenograft rejection was largely intravascular rather than associated with infiltrating inflammatory cells (21).…”
Section: Discussionsupporting
confidence: 77%
“…The importance of fgl2 to allograft rejection is supported first by the observation that expression of fgl2 correlates with rejection (6) and also by the fact that administration of neutralizing Ab to fgl2 diminished the pathological injury and improved graft survival in a similar fashion to that previously reported in murine hepatitis infection (20).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…FGL2 is expressed in several subsets of T-lymphocytes, including gut mucosal lymphocytes (Ruegg and Pytela, 1995) as well as activated hepatic endothelial cells and macrophages (Marsden et al, 2003). FGL2 is induced in type 1 lymphocytes by IFN signaling pathways, including irf1 (Hancock et al, 2004), which we found up-regulated in our array screen (see Supplementary Materials). Conflicting data from FGL2-deficient mice experiments show that FGL2 may or may not contribute to immunologically mediated thrombosis (Marsden et al, 2003;Hancock et al, 2004).…”
Section: Activity Of Immune Response/inflammationrelated Genes Duringmentioning
confidence: 70%